Effect of renin‐angiotensin‐aldosterone system blocking agents on progression of glomerulopathy in sickle cell disease. (21st November 2018) - Thrower, Ashley; Ciccone, Emily J.; Maitra, Poulami; Derebail, Vimal K.; Cai, Jianwen; Ataga, Kenneth I.
Summary: Although renin‐angiotensin‐aldosterone system (RAAS) blocking agents decrease albuminuria in short‐term studies, there is no evidence confirming their long‐term efficacy in sickle cell disease (SCD). In a single‐centre, retrospective study, we evaluated the long‐term effect of RAAS blocking agents on proteinuria and declining estimated glomerular filtration rates (eGFR). Eighty‐six patients on RAAS blocking agents for proteinuria, followed for a median of 2·28 years, were compared with 68 patients with proteinuria followed for 2·24 years who were not receiving such treatment. The log odds of proteinuria decreased over time in patients on RAAS blocking agents (β: −0·23, P = 0·03) and in the non‐treatment group (β: −0·54, P < 0·0001), but was not statistically different between both groups (β: 0·31, P = 0·063). The eGFR declined over time in patients on RAAS blocking agents (β: −2·78, P < 0·0001) and in those not on such treatment (β: −4·7, P < 0·0001), and was statistically different between both groups (β: 1·9, P = 0·0002). Baseline eGFR was associated with mortality (Hazard rato: 0·97, P < 0·0001), but RAAS blocking agents had no significant effect on mortality. These data suggest that RAAS blockade may slow the loss of kidney function in SCD.